Application of hazard functions to investigate recurrence after curative-intent resection for hepatocellular carcinoma. Issue 2 (February 2023) - Lima, Henrique A.; Alaimo, Laura; Brown, Zachary J.; Endo, Yutaka; Moazzam, Zorays; Tsilimigras, Diamantis I.; Shaikh, Chanza; Resende, Vivian; Guglielmi, Alfredo; Ratti, Francesca; Aldrighetti, Luca; Marques, Hugo P.; et al.
Abstract: Background: Defining patterns and risk of recurrence can help inform surveillance strategies and patient counselling. We sought to characterize peak hazard rates (pHR) and peak time of recurrence among patients who underwent resection of hepatocellular carcinoma (HCC). Methods: 1434 patients who underwent curative-intent resection of HCC were identified from a multi-institutional database. Hazard, patterns, and peak rates of recurrence were characterized. Results: The overall hazard of recurrence peaked at 2.4 months (pHR: 0.0384), yet varied markedly. The incidence of recurrence increased with Barcelona Clinic Liver Cancer (BCLC) stage 0 (29%), A (54%), and B (64%). While the hazard function curve for BCLC 0 patients was relatively flat (pHR: <0.0177), BCLC A patients recurred with a peak at 2.4 months (pHR: 0.0365). Patients with BCLC B had a bimodal recurrence with a peak rate at 4.2 months (pHR: 0.0565) and another at 22.8 months. The incidence of recurrence also varied according to AFP level (≤400 ng/mL: 52.6% vs. >400 ng/mL: 36.3%) and Tumor Burden Score (low: 73.7% vs. medium: 50.6% vs. high: 24.2%) (both p < 0.001). Conclusion: Recurrence hazard rates for HCC varied substantially relative to both time and intensity/peak rates. TBS and AFP markedly impacted patterns of hazard risk of recurrence.